(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Autonomous low power electric power plants working with variable speed energy sources or electric subsystems of cogeneration plants of some type need to increase the low speed or the low voltage of the system. In this paper the investigations and the results of the experiments conducted using different structures are given.